Environmental management of air, water, agriculture, and energy - Vasel-Be-Hagh, Ahmad; Ting, David S-K (CRC Press, 2019)
"Environmental Management of Air, Water, Agriculture, and Energy brings together the most current state of knowledge on four major elements for sustaining life on planet Earth: air, water, food, and energy. It examines how green technology aids in mitigating the global water, energy, and climate change crises, including the use of electrostatic force and green infrastructure. The concepts of underwater vegetation and aquatic cultivation, as well as vertical farms, are presented to spark discussion on emerging water-energy-food nexus lessons, experiences, and opportunities. This book takes a comprehensive global scale approach to examining potential future environmental scenarios and outcomes. Features: Analyzes the most recent research findings in each of the areas covered Synthesizes the state-of-the-art understanding Recommends ways to strive forward and to shape future research Serves as an educational tool for educators and students Supported by detailed examples and case studies, this book serves not only as an up-to-date source of information for environmental experts and researchers in the field, but also as an educational tool for relevant undergraduate and graduate courses. It is also suitable for industry professionals concerned with preserving planet Earth for generations to come"--